Molecular detection and identification of Leishmania infection in naturally infected sand flies in a focus of cutaneous leishmaniasis in northern Morocco - Es-Sette, Nargys (BioMed Central, 2014)
BACKGROUND: Cutaneous leishmaniasis is an infectious disease caused by various species of the flagellate protozoan Leishmania. During the past 20 years, cutaneous leishmaniasis has emerged as a major public health threat in Morocco. The main objective of this study was to study the occurrence of Leishmania infection in vectors and to identify sand fly blood meal sources in an endemic locality of cutaneous leishmaniasis within Sefrou province, where the vectors of leishmaniasis were still unknown. METHODS: 2650 sand flies were collected using CDC miniature light traps and identified morphologically. The identified sand flies were tested for Leishmania infection by nested PCR. The source of blood meal of 10 freshly engorged females: 6 Phlebotomus longicuspis and 4 Phlebotomus sergenti, was determined using the Cyt b sequence. RESULTS: The collected sand flies consisted of 10 species, seven of which belonged to the genus Phlebotomus and three to the genus Sergentomyia. The most abundant species was P. longicuspis, accounting for 72% of the total sand flies collected. In females of three P. longicuspis and four P. sergenti, Leishmania infantum and Leishmania tropica DNA was detected, respectively. The source of blood meal of engorged females showed that all sand flies tested fed on humans. CONCLUSIONS: We report for the first time the natural infection of P. longicuspis with L. infantum in Morocco. The high frequency of this species in this region, in addition to its anthropophilic character make P. longicuspis the putative vector of L. infantum in this cutaneous leishmaniasis focus where L. tropica is confirmed as the causative agent of the disease and P. sergenti as its vector. The presence of L. infantum, and its presumed vector in this area, makes this a site of high risk of visceral leishmaniasis, mostly because of the proximity of a focus of human and canine visceral leishmaniasis.